MEETING ZOOM SEBAGAI MEDIA PEMBELAJARAN TAHSIN AL-QUR’AN DI ERA PANDEMIK CORONAVIRUS DISEASE 2019 - Maududi, Mukhlish Muhammad; Moh. Supendi (E-journal Widya Non-Eksakta, 2019)
Appeals to maintain distance and prohibit direct contact and the increasing number of COVID-19 sufferers force all these activities to be carried out on-line using ommunication technology with various platforms as learning media. The purpose of this study is to describe the phenomenon of using Zoom Meeting as a medium for conducting UHAMKA Lecturer Al-Quran Study activities, during the Coronavirus Disease 2019 (COVID-19) pandemic, activities centered at home including worship, including recitation activities carried out through the Zoom Meeting application. This study uses a qualitative method with a phenomenological approach. Data collection techniques were carried out by in-depth interviews and literature studies to support the results of the interviews. From the research results, it is found that technology helps the learning process of the Koran to be more efficient, effective and more economical, the use of zoom communication media is different from conventional face-to-face communication patterns, namely users are more disciplined in terms of time but there is less warmth in communication.